2003
DOI: 10.1124/mol.63.6.1312
|View full text |Cite
|
Sign up to set email alerts
|

Agonist Actions of “β-Blockers” Provide Evidence for Two Agonist Activation Sites or Conformations of the Human β1-Adrenoceptor

Abstract: Previous work with 4-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
138
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 85 publications
(155 citation statements)
references
References 33 publications
15
138
2
Order By: Relevance
“…(22) The use of different doses of propranolol in these studies is critical due to the paradoxical and nonselective effects of propranolol on adrenergic receptors. (46) In our study, by selectively removing the b1-and b2-adrenergic receptors or both, we showed that b1-adrenergic signaling was the most important for cancellous and cortical responses to mechanical stimulation. Note, however, that we only found low expression levels of Adrb1 mRNA in osteoblasts from calvaria of WT mice.…”
Section: Discussionmentioning
confidence: 56%
“…(22) The use of different doses of propranolol in these studies is critical due to the paradoxical and nonselective effects of propranolol on adrenergic receptors. (46) In our study, by selectively removing the b1-and b2-adrenergic receptors or both, we showed that b1-adrenergic signaling was the most important for cancellous and cortical responses to mechanical stimulation. Note, however, that we only found low expression levels of Adrb1 mRNA in osteoblasts from calvaria of WT mice.…”
Section: Discussionmentioning
confidence: 56%
“…Through the high-affinity site b-blockers, including (À)-CGP12177, antagonize the effects of catecholamine. The low-affinity site usually appears to mediate the effects of NCPA (but see Baker et al, 2003), including those of (À)-CGP12177, and has low affinity for b-blockers (Kaumann, 2000;Konkar et al, 2000;Granneman, 2001;Lowe et al, 2002;Joseph et al, 2003). The two binding sites for (À)-[ 3 H]-CGP12177 (affinity ratio B500) were recently verified on recombinant Arg389-b 1 -adrenoceptors transfected at physiological density into CHO cells (Joseph et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…CGP 12177 inhibits isoprenaline-induced ␤1-adrenoceptor responses as a high affinity neutral antagonist; however, at higher concentrations (i.e., with lower affinity) it produces an agonist response which is relatively resistant to antagonism by classical ␤-antagonists (Pak and Fishman, 1996;Konkar et al, 2000a,b;Lowe et al, 2002;Baker et al, 2003b). Further studies from knockout animals and transfected cell system receptors showed that both pharmacological profiles were dependent upon the presence of only the ␤1-adrenoceptor and not a further subtype of ␤-receptor, hence the current two-state receptor model (Pak and Fishman, 1996;Kaumann and Molenaar, 1997;Kaumann et al, 1998;Cohen et al, 2000;Konkar et al, 2000a,b;Granneman, 2001;Kaumann et al, 2001;Baker et al, 2003b). This is very different from the human ␤2-adrenoceptor, where CGP 12177 is a typical partial agonist (i.e., similar K D values) from binding (0.14 nM), partial antagonism (0.09 -0.17 nM), and agonism (EC 50 0.22 nM; Baker et al, 2002).…”
mentioning
confidence: 99%
“…Furthermore, the plasma concentration of carvedilol (100 ng/ml ϭ 300 nM) used in human cardiovascular diseases is sufficient to activate this secondary site (Sawangkoon et al, 2000;Baker et al, 2003b). However, whereas the ␤1-low-affinity state appears to signal via G s -proteins in recombinant cell systems (Pak and Fishman, 1996;Konkar et al, 2000b;Baker et al, 2003b), this conformation may also couple to G i -proteins in rat heart and blood vessels (Kompa and Summers, 1999;Mallem et al, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation